A pointwise approximation theorem for linear combinations of Bernstein polynomials. (1996) - Guo, Shunsheng; Yue, Shujie; Li, Cuixiang; Yang, Ge; Sun, Yiguo
Abstract : Recently, Z. Ditzian gave an interesting direct estimate for Bernstein polynomials. In this paper we give direct and inverse results of this type for linear combinations of Bernstein polynomials.